The Effectiveness of Tactical Game Approach Through Handball Games on Decision Making and Manipulative Movement Skills of Elementary School Students - Khoerunnisa Azzahra; Agus Mahendra; Mukhlisin (Universitas Negeri Semarang, 2025)
This study aims to determine the effectiveness of the application of the Tactical Game Approach (TGA) through handball games on improving decision-making abilities and manipulative motor skills of elementary school students. The background of this study is because PE learning in elementary schools is still dominated by conventional approaches, making students less active and less involved in the game. This study used an experimental method with a one-group pretest-posttest design and involved 30 elementary school students selected through a purposive sampling technique. Data were collected using the Game Performance Assessment Instrument (GPAI) to measure decision-making abilities and the Test of Gross Motor Development-3 (TGMD-3) to measure manipulative motor skills during the pretest and posttest. The data obtained were analyzed using the non-parametric Shapiro-Wilk test to test normality and the Wilcoxon Signed-Rank Test to test differences in pretest and posttest results. The results showed an increase in the average score in both aspects studied. Based on the Wilcoxon test results, a significance value of 0.000 (p < 0.05) was obtained, which means there is a significant difference between the pretest and posttest results. The application of the Tactical Game Approach through handball games is effective in improving decision-making abilities and manipulative motor skills of elementary school students. Further research is recommended to use an experimental design involving a control group or compare the effectiveness of TGA with other learning models.